Abeta toxicity 1 - Masters, Colin L. (Henry Stewart Talks, 2011)
The amyloid plaque, Impact of delaying onset of AD, The amyloidocentric theory of Alzheimer's disease, Compelling evidence for the Abeta theory of AD, Delay onset of AD by 5 years, The best target for a disease-modifying drug, APP structure and domains, Iron-export ferroxidase activity of beta-amyloid precursor protein, Age at onset correlates with Abeta isoforms, Activation of PS1, Abeta amyloid, The mechanism of neurodegeneration, Abeta metal binding modes, Current working model of Abeta toxicity, Abeta amyloid protein: current model consistent with EXAFS, Metal-protein attenuating compound (MPAC) with moderate affinity for metals, Clioquinol (CQ, PBT1) the prototypic MPAC, PBT2: SAR based on rational drug design, CQ (PBT1) vs. PBT2, Alzheimer's disease Abeta-directed therapeutics in clinical development: drugs and biologics, Phase II results of Abeta targeting AD modifying drugs